2016 17th International Carpathian Control Conference (ICCC) 2016
DOI: 10.1109/carpathiancc.2016.7501056
|View full text |Cite
|
Sign up to set email alerts
|

An IoT based system for remote patient monitoring

Abstract: Internet of Things (IoT) is gaining more attention from last few decades. Nowadays, people are moving towards the IoT based systems for living their life luxuriously. Adoption of IoT in the field of healthcare sector is noticeable. Real time monitoring of patient is possible in better way using this technique. Due to integration of IoT, the quality of services in healthcare field is surpasses. Most of the time due to improper monitoring of patient's body parameters causes hazardous effects on patient's health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 14 publications
0
26
0
3
Order By: Relevance
“…Aynı zamanda, Micrososft SQL Server ilişkisel veritabanı [21][22], PostgreSQL ilişkisel veritabanı [23][24] ve SqlLite ilişkisel veritabanını kullanan uygulamalara da rastlanılmıştır [25]. SQL'in hız ve performans etkisi üzerine çalışan bazı araştırmacılar ise dosya tabanlı yerel sunucular [6] ve nesne ilişkisel veritabanı üzerine çalışmalar yapmışlardır [26]…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Aynı zamanda, Micrososft SQL Server ilişkisel veritabanı [21][22], PostgreSQL ilişkisel veritabanı [23][24] ve SqlLite ilişkisel veritabanını kullanan uygulamalara da rastlanılmıştır [25]. SQL'in hız ve performans etkisi üzerine çalışan bazı araştırmacılar ise dosya tabanlı yerel sunucular [6] ve nesne ilişkisel veritabanı üzerine çalışmalar yapmışlardır [26]…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…They found ZigBee as the best suited wireless data communication module because of its energy efficiency, security and less interference as compared to Bluetooth. Archip et al (2016) developed a prototype of remote patient monitoring for patients who undergone a surgery. The overall functionality of the system is done using RESTful based web interface (Singh et al 2015) and provides flexible mechanism to add new components.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the work in the state of the art have not demonstrated or their scalability to real-world use-cases, unfortunately. Archip et al (2016) work is promising as they demonstrated and evaluated the prototype but their use-case targeted post-surgery patients and the cost and complexity were not taken into consideration. This paper fills the gap by providing a solution that can be both implemented and scalable.…”
Section: Introductionmentioning
confidence: 99%
“…Intelligent and advanced healthcare monitoring at remote places such as public sectors, homes, offices, etc. can be advantageous and economic in order to avoid or reduce hospitalized readmissions [1], [2], [3], [4], [5]. In order to obtain a broad overview of the practical implementation of these technologies, current technical papers on remote patient monitoring using IoT technology were also researched.…”
Section: Literature Surveymentioning
confidence: 99%